L’assurance de responsabilité, dite « wrap-up » - Archambault, Pierre (Assurances)

(untitled) (HEC Montréal, 1984)
The author describes the “wrap-up” liability insurance policy. “wrap-up” indicates that it covers all the various parties involved in a major construction project, such as a large building. Mr. Archambault has often dealt with this policy, and his article is therefore of particular interest. He knows its avantages and drawbacks, and thus speaks with authority when he concludes: “We are quite sure that this policy will be more and more used for major construction projects. Needless to say, the purchase of a “wrap-up” coverage involves certain hazards and its negotiation should therefore be entrusted to specialists.”